War on war : Lenin, the Zimmerwald Left, and the origins of communist internationalism - Nation, R. Craig (E-Duke books scholarly collection., 1989)
The outbreak of World War I precipitated a schism in the international socialist movement that endures today. Heeding calls for "rational defense," the leading European socialist democratic parties abandoned their vision of peace and internationalism as an integral part of the struggle for social justice and set aside their view of interstate war as the clearest example of the irrational essence of competitive capitalism. Only the Zimmerwald Left, led by Lenin, continued to speak out for internationalism. R. Craig Nation utilizes sources in Dutch, French, German, Italian, Russian, and Swedish.